ETHICAL CONDUCT IN THE DIGITAL SPACE: AN ANALYSIS OF STUDENTS' LINGUISTIC POLITENESS IN ONLINE LEARNING AT ITB STIKOM BALI (A PRAGMATIC STUDY) - Desy Damayanthi, Ni Putu (International Journal of Instructions and Language Studies, 2025)
This study analyzes the level and patterns of linguistic politeness among ITB Stikom Bali students in online learning interactions, with the aim of understanding how interpersonal ethics are maintained in a fast-paced virtual environment. Using the Politeness Principle framework as a pragmatic approach, this study examines the utterances of 76 students in two general courses during one academic semester. The results of the analysis show that the level of linguistic politeness is not uniform: there is high compliance with the Maxim of Tact (89.6%), which indicates hierarchical awareness and polite lexical choices, but significant violations were found in the Maxim of Agreement (40.0%) and the Maxim of Generosity (38.4%). Thus, the level of politeness among students can be said to be relatively high in terms of respect for hierarchy, but scattered and inconsistent in terms of maintaining social relationships. This pattern reflects the influence of digital culture, which emphasizes time efficiency and speed, thereby shifting empathy and academic professionalism. This study recommends curriculum interventions to integrate humanistic digital ethics as a bridge between technical competencies and interpersonal skills in a technology-based campus ecosystem.